PAX5 is a tumor suppressor in mouse mutagenesis models of acute lymphoblastic leukemia - Dang, Jinjun; Wei, Lei; de Ridder, Jeroen; Su, Xiaoping; Rust, Alistair G; Roberts, Kathryn G; Payne-Turner, Debbie; Cheng, Jinjun; Ma, Jing; Qu, Chunxu; Wu, Gang; Song, Guangchun; et al. (Blood, 2015)
Alterations of genes encoding transcriptional regulators of lymphoid development are a hallmark of B-progenitor acute lymphoblastic leukemia (B-ALL) and most commonly involve PAX5, encoding the DNA-binding transcription factor paired-box 5. The majority of PAX5 alterations in ALL are heterozygous, and key PAX5 target genes are expressed in leukemic cells, suggesting that PAX5 may be a haploinsufficient tumor suppressor. To examine the role of PAX5 alterations in leukemogenesis, we performed mutagenesis screens of mice heterozygous for a loss-of-function Pax5 allele. Both chemical and retroviral mutagenesis resulted in a significantly increased penetrance and reduced latency of leukemia, with a shift to B-lymphoid lineage. Genomic profiling identified a high frequency of secondary genomic mutations, deletions, and retroviral insertions targeting B-lymphoid development, including Pax5, and additional genes and pathways mutated in ALL, including tumor suppressors, Ras, and Janus kinase-signal transducer and activator of transcription signaling. These results show that in contrast to simple Pax5 haploinsufficiency, multiple sequential alterations targeting lymphoid development are central to leukemogenesis and contribute to the arrest in lymphoid maturation characteristic of ALL. This cross-species analysis also validates the importance of concomitant alterations of multiple cellular growth, signaling, and tumor suppression pathways in the pathogenesis of B-ALL.